Coupling Cu2O clusters and imine-linked COFs on microfiltration membranes for fast and robust water sterilization - Shijia Luo; Jinglin Gao; Congcong Yin; Yanqiu Lu; Yong Wang (Nature Communications)
Abstract As bacterial contamination crises escalate, the development of advanced membranes possessing both high flux and antibacterial properties is of paramount significance for enhancing water sterilization efficiency. Herein, an ultrathin layer of TbPa (an imine-linked covalent organic framework) and nanosized Cu2O clusters, sequentially deposited onto polyethersulfone membranes, demonstrate exceptional water flux performance, reaching a permeance level of 16000 LHM bar−1. The deposited TbPa, generating uniformly distributed reduction sites under illumination, facilitates the uniform formation of Cu2O clusters. Furthermore, these anchored Cu2O clusters significantly optimize electron transport within the ultra-thin layer of TbPa, thereby enhancing the performance of the membrane in generating reactive oxygen species (ROS). Consequently, this membrane achieves a flux recovery rate exceeding 98.6% for flux losses caused by bacterial fouling and maintains consistent performance over 10 cycles. This work presents an effective strategy for accessing bactericidal membranes and provides insights into efficient and mild water sterilization.